Re-identification of Strains from Aspergillus Section Aspergillus and Description of Three Unrecorded Species from Korea - Anbazhagan Mageswari; Daseul Lee; Le Dinh Thao; Donghun Kang; Dong-Hyun Kim; Seung-Beom Hong (Mycobiology)
The section Aspergillus includes xerophilic fungi that are economically significant and broadly distributed in natural settings as well as human habitats and are recognized for their sustenance on substrates with low water activity. Accurate identification of fungal species is essential for any reliable advances in mycological research. In this study, 108 strains from the section Aspergillus, originating from Korea and conserved at the Korean Agricultural Culture Collection, were subjected to re-identification using a combined dataset that included partial sequences of β-tubulin (BenA), Calmodulin (CaM), and RNA polymerase II second largest subunit (RPB2) genes, along with their morphological characteristics. We confirmed the presence of 12 species among the 108 strains originally isolated from Korea. Of them, nine species have been formerly reported in Korea (Aspergillus chevalieri, Aspergillus cibarius, Aspergillus cumulatus, Aspergillus glaucus, Aspergillus montevidensis, Aspergillus proliferans, Aspergillus pseudoglaucus, Aspergillus ruber, and Aspergillus tonophilus), and 3 species (Aspergillus aurantiacoflavus, Aspergillus intermedius, and Aspergillus niveoglaucus) were found to be previously unreported to be isolated from Korea. Here, the detailed characteristic features of these three unexplored species are presented, including specific morphological traits, genetic variations, and ecological niches in Korea.